2017
DOI: 10.18632/aging.101334
|View full text |Cite
|
Sign up to set email alerts
|

Human longevity: 25 genetic loci associated in 389,166 UK biobank participants

Abstract: We undertook a genome-wide association study (GWAS) of parental longevity in European descent UK Biobank participants. For combined mothers' and fathers' attained age, 10 loci were associated (p<5*10−8), including 8 previously identified for traits including survival, Alzheimer's and cardiovascular disease. Of these, 4 were also associated with longest 10% survival (mother's age ≥90 years, father's ≥87 years), with 2 additional associations including MC2R intronic variants (coding for the adrenocorticotropic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
176
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(195 citation statements)
references
References 45 publications
13
176
0
Order By: Relevance
“…Gene names are as reported by discovery, and have been 159 coloured based on overlap between confidence intervals (CIs) of effect estimates. Note, rs151091095 160 near USP2-AS1 is a proxy (r 2 = 1.00) for rs139137459, the SNP reported by Pilling et al;rs113946246 161 near ANKRD20A9P is a proxy (r 2 = 0.97) for rs2440012, the SNP reported by Zeng et al;no proxies 162 could be found for 13:31871514_T_G. Dark blue -Nominal replication (P<0.05, one-sided test).…”
mentioning
confidence: 88%
“…Gene names are as reported by discovery, and have been 159 coloured based on overlap between confidence intervals (CIs) of effect estimates. Note, rs151091095 160 near USP2-AS1 is a proxy (r 2 = 1.00) for rs139137459, the SNP reported by Pilling et al;rs113946246 161 near ANKRD20A9P is a proxy (r 2 = 0.97) for rs2440012, the SNP reported by Zeng et al;no proxies 162 could be found for 13:31871514_T_G. Dark blue -Nominal replication (P<0.05, one-sided test).…”
mentioning
confidence: 88%
“…As the definition of heritable longevity was not yet established, the construction and application of the family selection scores have not yet been adopted as state of the art in longevity research. As such, the majority of genealogical 5, 6, 10–14, 45 and genetic studies 2426, 3134 focus only on single, and thus including sporadic, long-lived individuals (singletons), with some exceptions focusing for example on parental age 28, 29 or multiple siblings 7, 25 . In previous work, we showed that longevity defined as top 10% survivors or more extreme is transmitted to subsequent generations 16 .…”
Section: Mainmentioning
confidence: 99%
“…581 DNA methylation age was computed according to the algorithm described by Hannum as the independent variable. We also defined a weighted continuous genetic risk score 605 calculated as described in (Pilling et al, 2017) for these 10 SNPs and tested its associations 606…”
Section: Dna Methylation Analysis 554mentioning
confidence: 99%
“…Pilling et al, 2017). For parental attained age (Martingale residuals) a negative BETA = reduced hazard, i.e.…”
mentioning
confidence: 99%